New perspectives on the Bronze Age : proceedings of the 13th Nordic Bronze Age Symposium held in Gothenburg 9th to 13th June 2015 - Bergerbrant, Sophie; Wessman, Anna (Archaeopress Publishing Ltd, 2017)
This collection of articles helps to explain why the Bronze Age has come to hold such a fascination within modern archaeological research. By providing new theoretical and analytical perspectives on the evidence new interpretative avenues have opened, it situates the history of the Bronze Age in both a local and a global setting.